Penyuluhan Pencegahan Penularan Penyakit Malaria kepada Masyarakat di Desa Kampung Baru Kelurahan Galang Baru Kota Batam - Victor E.D. Palapessy (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Malaria is an infectious disease caused by parasites of the genus Plasmodium. It targets erythrocytes and manifests with symptoms such as fever, chills, anemia, and splenomegaly, either acutely or chronically, transmitted to humans through the bite of infected female Anopheles mosquitoes. Malaria remains a public health problem in many areas, including Kampung Baru Village, Galang Baru Subdistrict, Batam City. In order to fulfill the mission of community service, we have designed a comprehensive and sustainable education program to increase awareness and knowledge of the community about malaria. This program not only focuses on educating about the prevention and management of the disease but also directly involves active participation of the community in the learning and implementation process. Through collaboration with various parties, such as community leaders, health workers, and local leaders, we aim to create an environment that supports sustainable behavioral change in malaria prevention efforts. Additionally, we integrate a multidisciplinary approach in this program by addressing specific challenges faced in the local context, such as limited access to healthcare services, environmental conditions conducive to the breeding of malaria-carrying mosquitoes, and socio-economic factors influencing prevention and treatment efforts. Thus, this education program aims not only to reduce the burden of malaria in Kampung Baru Village and its surroundings but also serves as a tangible contribution to fulfilling the tri dharma activities of higher education institutions in the field of community service.